Unveiling a novel in-vitro model of skin inflammaging - Xu, Ying; Liu, Yue; Li, Junxiang; Li, Yao; Xu, Linlin; Dong, Kun; Lin, Xiao; Zhang, Tao (Frontiers in Medicine, 2025)
IntroductionSensitive skin is characterized by a disrupted skin barrier, making it prone to reacting to external stimuli, including UV exposure, air pollution, and cosmetic allergens. Sensitive skin tends to react with oxidative stress factors that could further lead to inflammation and subsequently result in inflammaging. However, there are almost no existing inflammaging models specifically for sensitive skin, highlighting the need to develop a method for screening anti-inflammaging ingredients and products.MethodsAn in vitro macrophage-fibroblast model was established to evaluate the anti-inflammaging effects of the ingredients. The M1 phenotype and aging-associated gene expression were assessed using qPCR to validate the inflammaging model. RNA sequencing was used to further elucidate the inflammaging mechanisms of the two validated ingredients.Results and conclusionA novel in-vitro model of sensitive skin inflammaging was developed by applying the supernatant of the M1 macrophage culture medium to induce cellular senescence in fibroblast cells, facilitating the screening of anti-inflammaging ingredients. In this model, supramolecular bakuchiol could promote collagen COL1A1 and COL3A3 production and inhibit inflammatory factors by enhancing the transcription of anti-inflammatory genes (PTX3, ADAM33, and PDLIM1), while Terminalia chebula extract inhibits cell senescence by reducing the transcription of MAP4K2 and the accumulation of the inflammatory factor CCL3.